Training on producing eucalyptus and betel leaf oil for dengue fever prevention - Wachidah Yuniartika; Liana Mangifera; Mitoriana Porusia; Dyaz Surya Ananta; Zuan Nun Alea; Aisyah Dani Hanifah (University of Merdeka Malang, 2024)
Dengue Hemorrhagic Fever (DHF) remains a significant public health issue in Indonesia and is endemic in nearly all provinces. The mortality rate from DHF continues to rise each year. To address this, health education on dengue fever prevention is essential. One preventive measure involves the use of natural ingredients. Betel leaves, in particular, can kill mosquito larvae due to the toxic substances they contain, which are especially harmful to mosquito larvae. Therefore, community service activities are necessary to raise awareness and provide practical solutions. This activity was conducted in Jetis Village, Sukoharjo, targeting 30Â women in the Family Welfare Program (PKK)Â from the local community. The implementation included the preparation of pre-tests and post-tests, as well as training sessions. The questionnaire used in this activity assessed participants' skills through a pretest, followed by training in making eucalyptus and betel leaf oil, and concluded with a post-test. The results showed a significant improvement in the participants' skills, with most moving from